Optimizing Nitrogen Fertilizer for Wheat Production in Moisture-Deficit Areas of Northern Ethiopia - Workat Sebnie; Ewunetie Melak; Tilahun Esubalew; Haymanot Lamesgn; Tesfa Asmelie; Messay Abera (JOURNAL OF TROPICAL SOILS, 2024)
Depleting soil nutrients is among the significant factors affecting production and productivity in Ethiopia. From the nutrients, nitrogen is the most yield-limiting, which governs wheat production. Therefore, the study was conducted to examine the effect of nitrogen on the yield and yield components of bread wheat varieties. The experiment was implemented in the 2019 and 2020 cropping seasons at Sekota and Lasta districts on the farmers’ field. The treatments consisted of a factorial combination of four levels of nitrogen (0, 46, 69, and 92 kg ha-1) and two varieties of wheat (Sekota-1 and Hibst), which were replicated three times in a randomized complete block design. Each treatment was provided with 23 kg ha-1 triple supper phosphate (P2O5). The study’s results indicated that grain and yield-related traits were significantly affected by nitrogen application. The increasing rate of nitrogen up to 92 and 69 kg ha-1 increases wheat grain and biomass yield by (150.3% and 54.1%) and (95.9 and 60%) in Sekota and Lasta districts, respectively. The highest grain yield (2562 and 2980 kg ha-1) was obtained from applying 92 and 69 kg ha-1 N at Sekota and Lasta, respectively. Therefore, applying 92 and 69 kg ha-1 N is the appropriate rate and recommended for the Sekota and Lasta districts, respectively.